Transgressing Motherhood: Media Reports on Infanticide. Issue 3 (4th March 2017) - Saavedra, Luísa; de Oliveira, João Manuel
ABSTRACT: This article seeks to understand the discourses on motherhood elicited by media in news articles dealing with infanticide. Applying thematic analysis, we studied news and online comments of a Portuguese newspaper. The analysis of infanticidal mothers reports two different images of these mothers both constructed and profiled by the media and the readers. Women are more penalized based on their perversity, living in better economic conditions, being employed and married, whether by the media or by the readers. They are absolved in accordance with their mental illnesses or poor social and economic backgrounds.